miRNA–mRNA Associated With Survival in Endometrial Cancer - Xu, Xiaofeng; Liu, Tao; Wang, Yijin; Fu, Jian; Yang, Qian; Wu, Jun; Zhou, Huaijun (Frontiers in Genetics, 2019)
Although various factors may contribute to its initiation and progression, the etiology and prognosis factors of endometrial carcinoma (EC) remains not fully understood. We sought to understand the role of changes in transcriptome during the progress of EC by exploring public datasets. The aberrant expression characteristics of EC based on RNA-Seq and miRNA-seq data from The Cancer Genome Atlas ( TCGA ) were analyzed. Kaplan-Meier analysis was performed to assess the relationship between differently expressed genes ( DEGs ) and patient survival. As a result, 320 out of 4613 differently expressed mRNAs ( DE mRNAs ) and 68 out of 531 differently expressed miRNAs ( DE miRNAs ) with a significantly poorer survival were determined. We predicted eight paired DE miRNAs and DE mRNAs through Targetscan. Patients with three out of the eight paired low rate of miRNA/mRNA (miR-497/EMX1, miR-23c/DMBX1, and miR-670/KCNS1) expression had a significant poorer survival. Furthermore, the simultaneous presence of these selected low miRNA/mRNA pairs occurred in most patients and resulted in a more significantly poorer survival rate. Luciferase reporter assay identified that EMX1 was a direct target of miR-497. Both low expression of miR-497 and overexpression of EMX1 were significantly associated with more advanced clinicopathologic characteristics (stage, tumor status, grade, and histology ) besides survival (all P value < 0.05 ). Multivariate analysis also demonstrated that miR-497 remained an independent prognostic variable for overall survival. In summary, we identified that a series of DE mRNAs and miRNAs, including eight paired DE miRNAs and mRNAs, were associated with survival in EC. Clinical evaluation of downregulated miR-497 and paired upregulated EMX1 confirmed the value of our prediction analysis. The simultaneous presence of low rate of these selected low miRNA/mRNA pairs (miR-497/EMX1, miR-23c/DMBX1, and miR-670/KCNS1) might have better prediction value. Therefore, further studies are required to validate these findings.